â€œCanva Youth Movementâ€ Training to Increase Youth Creativity on Graphic Design - Ashoumi, Hilyah; Hariono, Tholib; Widya, Anshori Aris; Sirojudin, Didin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem faced by faced by the youth in Pacarpeluk Village is the lack of basic skills in graphic design. basic skills that participants have in graphic design insights, lack of awareness about the lack of awareness of the career opportunities and market value of graphic design, lack of practical opportunities to develop graphic design skills, difficulties in marketing and distributing graphic design work by the youth of Pacarpeluk Village, and difficulties in building a social network or a community that accommodates to be able to support the potential of youth. So it is necessary to hold training to overcome this. The approach method for implementing this community service activity uses the Community Based Research (CBR) method. The stages of implementing the CBR method are identification of community needs, material planning, operational testing and operational assistance. Based on the results of the activities that have been carried out, as follows: Improve the skills of youth on graphic design media and add new insights for youth in graphic design.